Using reed to treat wastewater containing heavy metals - Son, Pham Huong; Nhu, Dang Xuyen; Lan, Nguyen Thi; Thanh Mai, Nguyen Thi (Academia Journal of Biology, 2012)
Industrial wastewaters are very complex and lead to water pollution if discharged untreated, especially due to its high heavymetal loading. In this study the constructed wetlands with free water surface in pilot scale designed for treatment of wastewater containing heavy metals has been monitored extensively with respect to removal of heavy metals. Metal concentrations in the influent wastewater, effluent and sediment were analyzed. The results indicated that reed was able to remove heavy metals directly from the contaminated water. All metals except Fe were efficiently removed in the CW, the metal concentrations in the effluent complied with standards for industrial wastewater (QCVN 24:2009/BTNMT-B). Removal efficiency varied between 77-93% for Fe and 99-100% for As, Zn, Pb, Cu and Sn. After 1 year of operation, the sediment in the area was not significantly contaminated with Zn, Cu, As, Pb, Fe, Sn